Economic importance of the Belgian ports: Flemish maritime ports, Liège port complex and the port of Brussels – Report 2009 - Claude Mathys (National Bank of Belgium, 2011)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Oostende, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels in the period 2004 - 2009, with an emphasis on 2009. Focusing on the three major variables of value added, employment and investment, the report also provides some information about social balance and the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. In terms of maritime cargo traffic, the downturn recorded during the last quarter of 2008 continued throughout 2009. Direct value added declined in all the ports in Flanders. Maritime branches as a whole contracted. Only the value added of the maritime branches in the port of Ostend remained stable. The non-maritime branches as a whole saw a contraction in all the Flemish ports. It was the port of Antwerp that suffered the most from the drop in the value added. Its maritime branches shrank by nearly one third. While the non-maritime branches were slightly down. The port of Ghent recorded a bigger decrease in the non-maritime branches. Conversely, the value added in the port of Zeebrugge fell more sharply in the maritime branches. Direct employment in the ports of Flanders as a whole declined during the year 2009. Except in Ghent, direct employment in the maritime branches fell in all the Flemish ports. Similarly, only one of them, the port of Ostend, recorded a rise in employment in the non-maritime branches. Thanks to this, it has been the only Flemish port to register direct employment growth. Investment decreased in all the ports in Flanders. The decline in investment was between one-sixth and one-fifth in the ports of Ghent, Antwerp and Zeebrugge. While Ostend recorded a cut of more than one third in its investment levels in 2009. The volume of cargo handled in the port of Liège decreased strongly in 2009. Direct value added and employment registered a significant decline. Maritime and non-maritime branches were down for both value added and employment. Thanks to the "other services" branch of activity, investment rose steadily. The volume of cargo handled at the port of Brussels declined in 2009. Value added in this port remained steady. But employment contracted slightly. After the growth seen in 2008, investment was down by more than a quarter. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2009.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments